Combination of Traditional Medicine and Synthesis Medicine Therapy for Hypertension and Diabetic Patients - Ersi Arviana Ihsan; Fitriwati Sovia; Erma Ewisa Oktresia; Tri Puspita Yuliana; Sulistia Ardyati; Arief Rafsanjani (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
Hypertension and diabetic are interrelated diseases affect atherosclerosis. This study aims to analyze the combination of traditional medicines and synthetic medicine with a job background for patients with hypertension and diabetic. Case-control study method retrieves patient data with medical records. Sampling was done with a purposive sampling technique of 30 respondents conducted in March-June at Labuhan Lombok Health Center. The results showed the percentage of diabetic patients was 26.67% for men and 73.33% for women with a background of 60% of traders, 20% of farmers, 13.3% of fishermen, and housewives of 6.7%. Furthermore, for hypertension patients, the percentage was 13.33% for men and 86.67% for women with a background of 40% of traders, 53.3% for farmers, 6.7% for fishermen. For traditional medicine used are Moringa oleifera L., Cucumis sativus L., jamu gendong, Averrhoa bilimbi L., Curcuma longa L., and Artocarpus camansi Blanco. Based on this, the risk factors for women are more generous than for men, and the use of a combination of drugs gives positive results in improving health.